Preliminary studies on the effect of polyethylene octene elastomer on polypropylene nanocomposite: mechanical properties and phase morphology - Hassan, Azman; Lim, J. W.; Wahit, Mat Uzir; Rahmat, Abdul Razak (2004)
The melf-direct intercalation method was employed to prepare rubber toughened polypropylene nanocomposites (RTPPNC). The blends composition was kept constant (PP+organocloly 6wt%) while the polyethylene octane (POE) content was varied between 0 and 20w% .Maleated PP (PP-g-MAH) was used as compatibilizer in the blend system. The POE used had 25wt% 1-octene content. X-ray diffractometer (XRD) revealed that an intercalation MMT silicate layer structure was formed in rubber-toughened polypropylene nanocomposite (RTPPNC). Izod impact measurements indicated that the POE addition led to a significant improvement in the impact strength of the RTPPNC, from 6.2 kJ /m2 in un-toughened PP/ Org-MMT nanocomposite to 17.8 kJ/m2 in RTPPNC containing 20wt% POE. However, the flexural modulus and flexural strength of the blends decreased with respect to neat PP as the weight fraction of POE was increased to 20wt%. Scanning electron microscope (SEM) was used for the investigation of the phase morphologry, rubber patlicles size and particle size distribution. SEM study revealed a two-phase morphology where POE as droplets dispersed finely and uniformly in the PP matrix.